Vaccines Directed Against Microorganisms or Their Products Present During Biofilm Lifestyle: Can We Make a Translation as a Broad Biological Model to Tuberculosis? - Flores-Valdez, Mario A. (Frontiers in Microbiology, 2016)
Tuberculosis (TB) remains as a global public health problem. In recent years, experimental evidence suggesting the relevance of in vitro pellicle (a type of biofilm formed at the air-liquid interface) production as a phenotype mimicking aspects found by M. tuberculosis-complex bacteria during in vivo infection has started to accumulate. There are still opportunities for better diagnostic tools, therapeutic molecules as well as new vaccine candidates to assist in TB control programs worldwide and particularly in less developed nations. Regarding vaccines, despite the availability of a live, attenuated strain (M. bovis BCG) since almost a century ago, its variable efficacy and lack of protection against pulmonary and latent disease has prompted basic and applied research leading to preclinical and clinical evaluation of up to 15 new candidates. In this work, I present examples of vaccines based on whole cells grown as biofilms, or specific proteins expressed under such condition, and the effect they have shown in relevant animal models or directly in the natural host. I also discuss why it might be worthwhile to explore these approaches, for constructing and developing new vaccine candidates for testing their efficacy against TB.